Evaluation of the rheological properties in solution and molten state of hyperbranched polyester polyols obtained of first and second generation (2020)
The hyperbranched polyesters have gain great attention since these materials have smallest hydrodynamic dimensions, high functionality, good solubility and they may be modified for obtaining compounds for specific applications. There are few reports about the rheological properties on the solution and molten state of the hyperbranched polyesters polyols obtained of the first and second generation, especially those prepared from dimethyl propionic acid and pentaerythritol. Thus, the aim of this study is to evaluate the rheological properties in solution and molten state of these materials. Furthermore, the hydrodynamic dimensions by dynamic light scattering by using dimethyl formamide and dimethyl sulfoxide as solvents also were analyzed. The hydrodynamic dimensions on volume of the hyperbranched polyesters polyols obtained of second generation by using dimethyl formamide as solvent were greater than those of first generation, but the behavior was different when was used dimethyl sulfoxide as solvent. Furthermore, these materials exhibited aggregations. The rheological behavior in solution showed that all samples exhibited lowest viscosity and a Newtonian region between 1 and 60 s−1, then this behavior changed to shear thickening. By rheological analysis in molten state was evidenced a shear-thinning behavior to these materials.